Integrating occupational health and safety data digitally using building information modelling - uses of BIM for OHS Management - Tender, M. (2022)
Utilization of BIM (Building Information Modelling) for Occupational Health and Safety (OHS) purposes is a current trend but, as yet, there is not a complete list of its uses and potential. The main objective of this paper is to gather information about the main uses of BIM for improving OHS management. A methodlogy was adopted based on requirements defined in a European Directive covering the implementation of minimum safety and health requirements at temporary construction sites. As a result of the analysis carried out the following main findings were drawn. Integrating OHS data digitally using BIM is a task that requires the efforts of all stakeholders. The results of the study conducted show that this approach can revolutionize the integration of OHS information through the use of BIM for managing data in the areas identified. Revealing ways in which BIM can be used for improving OHS management will provide construction stakeholders with a better understanding of BIM in terms of the benefits, limitations, and barriers. This has the potential to result in a paradigm shift in the prevention of work accidents.